2022
DOI: 10.1101/2022.12.19.521110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single nucleus and spatial transcriptomic profiling of human healthy hamstring tendon

Abstract: The molecular and cellular basis of health in human tendons remains poorly understood. Amongst human tendons, the hamstrings are the least likely to be injured or degenerate, providing a prototypic healthy tendon reference. The aim of this study was to define the transcriptome and location of all cell types in healthy hamstring tendon. We profiled the transcriptomes of 10,533 nuclei from 4 healthy donors using single-nucleus RNA sequencing (snRNA-seq) and identified 12 distinct cell types. We confirmed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Recent studies have revealed heterogeneity in adult tendon cell populations as well as identified noninstrinsic cell types in the tissue such as pericytes, immune, and endothelial cells 28,29,43,44 . A commonality across species with these datasets is the presence of tendon cell clusters with more prototypical tendon markers (i.e., Scx , Mkx , Tnmd ) and those enriched for matrix components such as Col1a1/a2 , but devoid of these characteristic tendon markers 45,46 . Some of these non Scx / Mkx expressing cell clusters have characteristics of fibro‐adipogenic progenitors (FAPs), including increased expression of Col3a1 , Ly6e , and Pdgfra 28,45 .…”
Section: Unbiased Gene Discovery Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have revealed heterogeneity in adult tendon cell populations as well as identified noninstrinsic cell types in the tissue such as pericytes, immune, and endothelial cells 28,29,43,44 . A commonality across species with these datasets is the presence of tendon cell clusters with more prototypical tendon markers (i.e., Scx , Mkx , Tnmd ) and those enriched for matrix components such as Col1a1/a2 , but devoid of these characteristic tendon markers 45,46 . Some of these non Scx / Mkx expressing cell clusters have characteristics of fibro‐adipogenic progenitors (FAPs), including increased expression of Col3a1 , Ly6e , and Pdgfra 28,45 .…”
Section: Unbiased Gene Discovery Methodsmentioning
confidence: 99%
“…There are several current platforms, including 10X Genomics Visium Spatial gene expression, Merscope (MerFISH; Vizgen), and GeoMx/CosMx (Nanostring), each with differing strengths (reviewed in Williams et al 48 ). Published and preprint studies in human and mouse have utilized the 10X Visium platform to show spatial distributions of cell types, including in mouse, cell cluster localization over healing stages 49 and in humans, specific fibroblast cell subtypes (MKX vs. PDGFRA) or myotendinous junction cells 44,46,50 …”
Section: Unbiased Gene Discovery Methodsmentioning
confidence: 99%
See 2 more Smart Citations